The Role of Geomorphic Controls on the development of defensive networks along the Western Front during the Great War: Case study of Champagne and Argonne (France) - Taborelli, P; Devos, A; Laratte, S; Brenot, J (Scientia Militaria - South African Journal of Military Studies, 2018)
The Great War was marked on the western front mainly by a war of position (for 40 out of the 51 months of the conflict) along the 750 km of the front area from Flanders to Alsace. The objective of this article is to understand the spatial organisation of defence networks in the eastern part of the Champagne region (Champagne sèche), the Vallage d’Aisne and in the Argonne region in 1918 by means of an analysis of geographical information system (GIS)-processed trench maps. This article presents a methodology, involving the transfer of fire trenches, communication trenches and vegetation, integrated into a geodatabase, and then cross-referenced with the digital terrain model (DTM). This comparison of three distinct regions with a chalky plateau (Champagne sèche), a wet plain (Vallage d’Aisne) and a sandy plateau covered with forests (Argonne), not only makes it possible to qualify the role of geographical conditions on the Great War but also to quantify the defence networks.